2010
DOI: 10.4314/ajid.v3i1.55076
|View full text |Cite
|
Sign up to set email alerts
|

Hand hygiene and health: an epidemiological study of students in Amravati

Abstract: Hands may be the most important means by which enteric pathogens are transmitted. Skin hygiene particularly of the hands, has been accepted as a primary mechanism to control the spread of infectious agents. Therefore the present study was undertaken to evaluate the number and type of enteric bacterial pathogens associated with hands. A total of 160 hands swab samples of 80 students of KG, PS, SS, UG, and PG were analyzed. Pathogens were isolated from hands includes Escherichia coli (22%), Pseudomonas aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
5
8
0
1
Order By: Relevance
“…Another recent study carried out in Kenya [19] revealed that 25% of tested products were showing their activity against only 33% of the tested organisms and an indefinite number of the antiseptics were not effective at all against any of the test organism. Results checked at 50% concentration in which almost not all the sanitizers except Sanitizer Hiclean, Biotol and Antibacterial hand gel exhibited any activity against any tested organism, which supports the findings of [17] who showed that antibacterial activity of most of the hand sanitizers decreases with increase in dilution or decrease in its concentration. Our study had few limitations as well that we did not test all the known hand sanitizers at District Abbottabad for the reason that they were not available in the market at that time.…”
Section: Susceptibility Of Microorganisms Against Sanitizers At 50% Csupporting
confidence: 85%
“…Another recent study carried out in Kenya [19] revealed that 25% of tested products were showing their activity against only 33% of the tested organisms and an indefinite number of the antiseptics were not effective at all against any of the test organism. Results checked at 50% concentration in which almost not all the sanitizers except Sanitizer Hiclean, Biotol and Antibacterial hand gel exhibited any activity against any tested organism, which supports the findings of [17] who showed that antibacterial activity of most of the hand sanitizers decreases with increase in dilution or decrease in its concentration. Our study had few limitations as well that we did not test all the known hand sanitizers at District Abbottabad for the reason that they were not available in the market at that time.…”
Section: Susceptibility Of Microorganisms Against Sanitizers At 50% Csupporting
confidence: 85%
“…Oniya et al, (2006) isolated microorganisms transmissible through hand-shake and also reported prevalence of microorganisms was higher in primary and secondary school students than in the under graduate students. The reduction in the number of pathogens after hand washing was also reported by Tambekar et al, (2009).…”
Section: Resultssupporting
confidence: 53%
“…Ray et al, (2009) observed a decrease in colony count following hand washing with soap in 60% of the samples. Tambekar et al, (2009) also observed highest bacterial contamination (70%) was observed on the hands of the KG students followed by 67% on hands of primary students, 66% on secondary students, 64% on PG students and least (57%) on the hands of under graduate students. Ray et al, (2011) found that hand swab samples of 61% children harbours potential pathogens before taking food, also reported presence of pathogenic microbes on the hands of the students which included S. aureus, E.…”
Section: Resultsmentioning
confidence: 72%
“…Food handlers can easily contaminate food with Staphylococcus aureus (common cause of food poising) if they do not wash their hands properly after using toilet and after making contact with their nose [22]. Tambekar et al also reported the reduction in the number of pathogens after hand washing [23]. …”
Section: Discussionmentioning
confidence: 99%